Chemokines regulate hippocampal neuronal signaling and gp120 neurotoxicity - Meucci, Olimpia (The National Academy of Sciences, 1998)
The HIV-1 envelope protein gp120 induces apoptosis in hippocampal neurons. Because chemokine receptors act as cellular receptors for HIV-1, we examined rat hippocampal neurons for the presence of functional chemokine receptors. Fura-2-based Ca imaging showed that numerous chemokines, including SDF-1α, RANTES, and fractalkine, affect neuronal Ca signaling, suggesting that hippocampal neurons possess a wide variety of chemokine receptors. Chemokines also blocked the frequency of spontaneous glutamatergic excitatory postsynaptic currents recorded from these neurons and reduced voltage-dependent Ca currents in the same neurons. Reverse transcription–PCR demonstrated the expression of CCR1, CCR4, CCR5, CCR9/10, CXCR2, CXCR4, and CX(3)CR1, as well as the chemokine fractalkine in these neurons. Both fractalkine and macrophage-derived chemokine (MDC) produced a time-dependent activation of extracellular response kinases (ERK)-1/2, whereas no activation of c-JUN NH(2)-terminal protein kinase (JNK)/stress-activated protein kinase, or p38 was evident. Furthermore, these two chemokines, as well as SDF-1α, activated the Ca- and cAMP-dependent transcription factor CREB. Several chemokines were able also to block gp120-induced apoptosis of hippocampal neurons, both in the presence and absence of the glial feeder layer. These data suggest that chemokine receptors may directly mediate gp120 neurotoxicity.